Chinese University EFL Students’ Perceptions of Learner Autonomy in Language Learning - Wei, Qiwei; Siriyothin, Peerasak; Lian, Andrew-Peter (Widya Mandala Catholic University Surabaya, 2018)
This paper explores Chinese university EFL students’ perceptions of learner autonomy in language learning through a digital storytelling intervention. The survey aims to investigate whether students’ learner autonomy was developed through the intervention and compared the perceptions of students of two different language performance levels. The principal measuring instruments were a questionnaire, a pretest, a posttest and student diaries. The results of the survey indicated that students’ learner autonomy was developed to some extent through the intervention and that there were significant differences between successful and less successful learners, as regards their opinions of learner autonomy. It is worth noting that after the intervention, a large proportion of students were in favor of autonomous approaches than before. A significant number of students expressed the desire, in their diaries, to work autonomously rather than study passively. The survey reflects that success is related to autonomy. Autonomy therefore means success. Success is created by autonomy and vice versa.